2021
DOI: 10.1124/jpet.121.000736
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous and Intramuscular Allopregnanolone for Early Treatment of Status Epilepticus: Pharmacokinetics, Pharmacodynamics, and Safety in Dogs

Abstract: Allopregnanolone (ALLO) is a neurosteroid that modulates synaptic and extrasynaptic GABA A receptors. We hypothesize that ALLO may be useful as first-line treatment for status epilepticus (SE). Our objectives were to 1) characterize ALLO pharmacokineticspharmacodynamics following intravenous (IV) and intramuscular (IM) administration and 2) compare IV and IM ALLO safety and tolerability. Three healthy dogs and two with a history of epilepsy were used. Single ALLO IV doses ranging from 1-6 mg/kg were infused ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 36 publications
0
9
1
Order By: Relevance
“…We obtained estimated Cmax values in the range of 1500-3000 ng/mL, validating our modeling. The Cmax value predicted by simulation in the earlier study 22 for a 1 mg/kg dose (~1000 ng/ml) is below the range obtained in the present study, likely because the dose was infused over 5 min rather than as a rapid bolus injection as was done here.…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…We obtained estimated Cmax values in the range of 1500-3000 ng/mL, validating our modeling. The Cmax value predicted by simulation in the earlier study 22 for a 1 mg/kg dose (~1000 ng/ml) is below the range obtained in the present study, likely because the dose was infused over 5 min rather than as a rapid bolus injection as was done here.…”
Section: Discussioncontrasting
confidence: 90%
“…Therefore, we evaluated the cardiopulmonary safety of intravenous ALLO delivered alone or shortly after intravenous MDZ in two dogs. The dose of ALLO (1 mg/kg) was selected based on a two‐compartment model using results from a prior study in dogs 22 . We intended to target a C max value of approximately 2000 ng/ml because peak plasma concentrations of ALLO of approximately 600–2000 ng/ml can effectively terminate benzodiazepine‐refractory SE in rodent models 17,23 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Vuu et al ( 387 ) reported the pharmacokinetics, pharmacodynamics, and safety of a new cyclodextrin-based i.v. formulation of allopregnanolone in healthy and epileptic dogs to develop this formulation for early treatment of SE.…”
Section: Use Of Dogs As a Translational Model In Epilepsy Research An...mentioning
confidence: 99%
“…In the dog study, the rapid onset of effect of allopregnanolone after i.v. infusion suggested that this drug may be useful in the early treatment of SE ( 387 ). Overall, these various studies establish the dog as a viable clinical model of human SE.…”
Section: Use Of Dogs As a Translational Model In Epilepsy Research An...mentioning
confidence: 99%
See 1 more Smart Citation